Community before self : seventy years of making waves - Burnham, Malin; Malone, Michael S. (Michael Shawn), 1954- (Advantage, member of Advantage Media Group, 2016)
When Malin Burnham gifted funds toward the construction of the new San Diego Yacht Club Junior Sailing Center, he stipulated that a list of “Virtues of Excellence” be permanently attached to the building and that these virtues be taught on an ongoing basis to the junior sailing participants. These virtues include dedication, teamwork, and commitment, and they are the result of lessons learned in Malin's life and career. Community Before Self details these virtues and explains how anyone can live a life of integrity and purposeful giving. Regardless of income, political views, or age, everyone can contribute toward enhancing their community by volunteering their time and effort. -- Publisher's description.